Makna Simbol dan Bahasa Seni Beladiri Suliwa - Anggi Indri Yani; Fitriana Poerana, Ana; Nurkinan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Padepokan Suliwa Karawang was founded on 8 October 2017 by H. Karta Wiratma, Suliwa is a vital part of the local cultural heritage with a focus on martial arts. With the main aim of developing and preserving arts and culture, Suliwa is actively involved in activities such as discussions, participation in community events, and a YouTube channel. Through qualitative research using an ethnographic communication approach and the application of George Herbert Mead's Symbolic Interaction Theory and Dell Hymes' Speaking Theory to understand human communication in a social context, Suliwa succeeded in forming a unity with the participants who practice the basic principles in line with the Siliwangi Kingdom, namely